2020
DOI: 10.1177/0269215520963855
|View full text |Cite
|
Sign up to set email alerts
|

Can the early use of botulinum toxin in post stroke spasticity reduce contracture development? A randomised controlled trial

Abstract: Objective: Does early treatment of spasticity with botulinum-toxin (BoNTA), in (hyper)acute stroke patients without arm-function, reduce contractures and improve function. Design: Randomised placebo-controlled-trial Setting: Specialised stroke-unit. Participants & Intervention: Patients with an Action Research Arm Test (ARAT) grasp-score⩽2 who developed spasticity within six-weeks of a first stroke were randomised to receive injections of: 0.9%sodium-chloride solution (placebo) or onabotulinumtoxin-A (trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 26 publications
0
30
2
2
Order By: Relevance
“…Botulinum toxin type A (BoNT-A) is a recommended treatment for PSS [ 10 , 11 , 12 ]. Despite the growing evidence for early treatment of PSS [ 13 , 14 , 15 ], BoNT-A is usually administered to chronic stroke patients in routine clinical practice [ 16 , 17 ], probably because of the variable prevalence of PSS during the first year after onset and because the published literature about BoNT-A for PSS reports mainly on treatment during the chronic phase [ 3 ]. With this study, we wanted to determine whether the time between stroke onset and initial BoNT-A injection had an effect on outcomes after treatment for PSS in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum toxin type A (BoNT-A) is a recommended treatment for PSS [ 10 , 11 , 12 ]. Despite the growing evidence for early treatment of PSS [ 13 , 14 , 15 ], BoNT-A is usually administered to chronic stroke patients in routine clinical practice [ 16 , 17 ], probably because of the variable prevalence of PSS during the first year after onset and because the published literature about BoNT-A for PSS reports mainly on treatment during the chronic phase [ 3 ]. With this study, we wanted to determine whether the time between stroke onset and initial BoNT-A injection had an effect on outcomes after treatment for PSS in routine clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in our retrospective study (12), we found that stroke survivors who received BoNT injections at an earlier time had much longer lasting effects than those who received injections at a late date. Taken together, these studies have supported the benefits of early spasticity intervention after stroke (5,(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 60%
“…In contrast, passive torques were significantly higher and passive range of motion of wrist and finger extension was significantly smaller in the affected limb than the contralateral limb in those who received BoNT injections to these muscles, on average, 4 and 1/2 years ago [43]. In another study [44], stroke subjects received either BoNT or placebo (normal saline) injections when spasticity was first detected in the arm flexors. The mean time to injections was 18 days after stroke.…”
Section: Bont Effects On Elbow Flexor Spastic Hypertoniamentioning
confidence: 98%